تصحيح فرض 1 دورة 1 الثال


تصحيح 

تمرين1

           

A          = ( 4x +  √13 ) ( 4x -  √13 ) -  ( 6x + 5 )                       

=    ( 4x )2 -  ( √13 )2 - [ ( 6x)2 -  2X 6x X 5 + 52 ]       

=   16x 2 -  13  - [36x2 -   60x  +25 ]                            

=   16x 2 -  13  - 36x2 +   60x  -25                             

=   16x 2  - 36x2 +   60x  -25    -  13                           

=   -20x 2  +   60x    -  38                                             

                                     

B = ( 2x - 3 )2  -  ( 2x - 1 ) ( 4x + 3 )                                                                                                                   

= [( 2x)2-2  X2x  X  3 + 32 ] -  ( 2x  X  4x +2x  X  3 - 1 X  4x  -  1 X  3 )                                                        

= 4x2-12x   + 9  -  ( 8x2 +6x  -  4x  - 3 )                                                                                                           

= 4x2-12x   + 9  -  8x- 2x + 3                                                                                                                       

 = 4x2 - 8x2 - 2x  -12x  +  3   + 9                                                                                                                       

 =  - 4x -14x  +12                                                                                                                                            

تمرين2

 

C = 81 x4  -  16                                                                                                                                        

=( 9x2)2  - 42                                      

=( 9x2  - 4 )( 9x2  +4 )                         

 

D      = 25 x2  -  70 x   + 49 + ( 6x  -  1 ) ( 7 - 5x )            

                  = (5 x)2  -  2 X 5X 7x   + 72 + ( 6x  -  1 ) ( 7 - 5x )            

= (5 x  -   7)2  + ( 6x  -  1 ) ( 7 - 5x )                

= (5 x  -   7)2  +[ -( 6x  -  1 ) ( 5x - 7)]               

= (5 x  -   7)2  -( 6x  -  1 ) ( 5x - 7)                    

= (5 x  -   7)[ ( 5x - 7) -( 6x  -  1 )   ]                   

= (5 x  -   7) ( 5x - 7 - 6x  +  1 )                           

= (5 x  -   7) ( - x  -6 )                                         

                      

E      =   ( 3x + 4 )2  -  2 ( 6x2  +  8x )  +  4x2                     

= ( 3x + 4 )2  -  2 X[ 2x ( 3x  +  4 ) ] +  4x2        

= ( 3x + 4 )2  -  2 X2x ( 3x  +  4 ) +  4x2            

= ( 3x + 4 )2  -  2 X2x ( 3x  +  4 ) +  (2x)2        

= ( 3x + 4 -2x )2                                                    

=   ( x + 4 )2                                                            

                               

تمرين 3

 

    F =  [ ( a-1 b2 ) -3a4b-2 ]    /    (a2b-1 ) 5                                                                                                                                                                                                                        

                          =[ ( a-1)-3( b2 ) -3a4b-2 ]   /   (a2 )5 (b-1 ) 5                                                                                                                             

                          = [ a3 b -6a4b-2 ]    /     a10 b-                                                                                                                                                                                                    

                           =  a3+4-10 b-6-2+5     

                          =  a-3 b-3                                                                                                

                          =  (ab)-3             

 

أحسب هذا العدد إذا علمت أن

a = 10 -3             و              b = 122      

                   

F =   (10-3 10 2 ) -3                     

=   (10-1 ) -3                     

                =  103            =   1000                       

تمرين 4

 

G         =     56 x 25  +  28                                                                                                                                                                                    

= 7X8 X 25  +  28  

= 7X23 X 25  +  28

= 7X23 +5  +  28      

= 7X28  +  28           

=  28 (7 +  1)            

=  28 x8                     

=  28x23                    

= 211                               

H     = 5-2 + [  5-2  + ( 25 / 24) -1 ] -7                                       

= 1/25 + [ 1/25  + 24/25 ] -7                                   

= 1/25 + [25 /25 ] -7                                               

= 1/25 + [1 ] -7                                                        

= 1/25  + 1                                                             

= 1/25  + 25/25                                                  

= 26/25                                                             

 

                        

تمرين 5

 

96000 x 10-20                                                                         

I         =            ________________                                                                   

0,00000025                                                                           

 

 

 

 

 

9,6x104 x 10-20                                                                         

I         =            ________________                                                                      

2,5 x 10-7                                                                           

 

 

 

9,6x104 x 10-20                                                                         

I         =            ________________                                                                      

2,5 x 10-7                                                                                 

 

I  =   (9,6/ 2,5)) x104 x10-20x107

=   (96/ 25)) x 104x 10-20x107

=   3,44 x  10-11                        

 

www.hassan.ab.ma

Welcome To My Website
hassan.ab.ma © 2017.Free Web Site